Influence of social support on technophobia in older adults in urban communities: the mediating role of self-efficacy and e-health literacy, a cross-sectional study - Jin Li; Chen Wang; Dan Luo; Yan Shi; Hua Qing Guo; Zhi Guang Duan (BMJ Open)
Objectives To explore the chained mediating role of self-efficacy and e-health literacy in the association between social support and technophobia in older adults in urban communities.Design A cross-sectional study conducted from June 2023 to April 2024.Setting This study was conducted in three districts of Taiyuan City, Shanxi Province, China.Participants The study enrolled 1658 older adults (> 60 years old) in urban communities in Taiyuan.Methods The analyses included assessments using the technophobia, e-health, self-efficacy and social support scales, and the mediating effects of these indices were investigated using Model 6 in SPSS V.26.Results The level of technophobia in older adults was found to be moderately high. Technophobia was negatively correlated with social support, self-efficacy and e-health literacy. Stepwise regression analysis showed that age, residential situation, health and the frequency of electronic device use were risk factors for technophobia (p<0.05). Social support could influence technophobia directly (β=−0.266). In addition, self-efficacy (β=−0.080) and e-health literacy (β=−0.098) significantly mediated the relationship between social support and technophobia.Conclusion Social support was found to affect technophobia in older adults via the independent or chained mediating effects of self-efficacy and e-health literacy.